ANALISIS PENERAPAN EDUKASI PERSIAPAN PERSALINAN DALAM PENINGKATAN KESIAPAN PERSALINAN PADA IBU HAMIL - Siti Nurjana A; RR Viantika Kusumasari; Fitri Dian Kurniati; Suib; Muskhab Eko Riyadi (Jurnal Ilmiah Keperawatan, 2024)
Background: Childbirth is a natural process that all pregnant women will go through. The mental preparation of the birthing mother is very necessary to face the unpredictable process of childbirth. Childbirth readiness will help the mother to be more willing to face her birth smoothly, confidently, and not feel anxious. Mothers need adequate knowledge to carry out a pregnancy well and prepare for childbirth well. Health education about birth readiness for pregnant women must be provided to minimize trauma. Objective: The aim of this research is to analyze the application of childbirth education to pregnant women with birth readiness nursing problems. Method: Descriptive research with a case study approach was used in this research. Results: The research results showed that there was a change in the level of knowledge of respondents before and after being given education. The respondent's level of knowledge increased after being given education with the respondent's knowledge level being in the good category. Conclusion: Based on the research results, it can be concluded that there is an increase in knowledge regarding childbirth readiness by providing childbirth education to pregnant women.